PENGARUH DEVIDEND PAYOUT RATIO, PRICE TO BOOK VALUE RATIO, DAN PRICE TO EARNINGS RATIO PADA RETURN SAHAM (Studi Empiris Pada Perusahaan Manufaktur Periode 2017-2020) - Innes Septya Putri; Nur Diana; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The purpose of this study was to determine the Dividend Payout Ratio (DPR) and its effect on stock returns of manufacturing companies, Price To Book Value Ratio (PBV) on stock returns of manufacturing companies, and Price To Earnings Rational (PER) on stock returns of manufacturing companies. The population used in this study were manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2020. The sample in this study was 12 companies sampled in 2019 to 2020. The research method used to analyze the multiple linear regression test with t as a hypothesis tester. The results of this study prove that the Dividend Payout Ratio, Price To Book Value Ratio, and Price To Earnings Rational together or simultaneously have a positive and significant effect on Stock Return. Kata kunci: Deviden Payout Ratio (DPR), Price To Book Value Ratio (PBV), Price To Earnings Rational, return saham.